Exploring academic article introductions from a paleontology community of practice through genre analysis - Cervo, Nathieli Cipolat; Marcuzzo, Patrícia (The ESPecialist, 2025)
Paleontology is the science which studies the evolutionary process of the species that inhabited Earth in the past. In the Brazilian state of Rio Grande do Sul, the Centro de Apoio à Pesquisa Paleontológica da Quarta Colônia da Universidade Federal de Santa Maria (CAPPA/UFSM) plays a fundamental role in the region. This study investigates the rhetorical organization of the Introduction sections of 22 articles written in English and published by the members of CAPPA/UFSM. They were analyzed based on Swales’ (1990; 2004; Swales; Feak, 2012) CARS model. Results show the sample investigated follows a general organization of Introduction in academic articles, which reinforces the moves and steps classified as “obligatory” by the CARS model. We also found variations regarding moves and steps, thus revealing some specific characteristics of the discipline of Paleontology represented in the academic articles of CAPPA/UFSM.